Clinical examination and differential diagnosis of skin lesions - Lipsker, Dan (Springer Paris, 2013)
Conceived as a guide for practitioners in their work in dermatology, this book is unique in its approach. From cutaneous signs to the richness of differential diagnosis, it guides practitioners through every step, from semiological analysis to diagnosis. The aim is to provide readers with the essentials of relevant dermatological reasoning. The first part of the book focuses on physical examination and on recognizing basic lesions, the practitioner's building blocks. The diseases requiring understanding are then described in the form of a richly illustrated atlas, in which each diagram has been chosen as an exemplary educational tool. In the final part, differential diagnosis is proposed in the form of various tables summarizing the different cutaneous signs, providing readers with a complete toolkit to assist with diagnosis. This book will give trainee dermatologists, general physicians and internists the knowledge they need to identify basic lesions and a complete and detailed overview of the various diseases they are likely to encounter. At the same time, experienced dermatologists will find this book a valuable reference work for differential diagnosis.